The Application of Artificial Intelligence in Enhancing Legal Protection for Patients in Dental Practice: A Positivist Perspective - Rika Noviantini; Zainal Arifin Hoesein (Journal Research of Social Science, Economics, and Management, 2024)
Legal protection for patients in dental practice is becoming increasingly important with advancements in technology, including artificial intelligence. Positivism provides a framework for analyzing this protection, as outlined in Article 276 of Law Number 17 of 2023 concerning Health, which guarantees patients' right to complete information regarding their health condition and the medical procedures to be performed. However, challenges in implementing regulations often arise, particularly regarding the lack of clarity in the information provided by dentists to patients. The purpose of this study is to analyze the application of artificial intelligence in enhancing legal protection for patients in dental practice, as well as to explore legal protections for patients in dental practice from a positivist perspective. The research method used is normative juridical, using a statutory approach and an analytical approach. The research findings indicate that the application of AI in dentistry enhances legal protection for patients by improving diagnostic accuracy and reducing medical errors. AI also supports better data management and decision-making while increasing transparency and accountability. From a positivist perspective, the emphasis on clear regulations is crucial for protecting patients' rights, ensuring that AI not only improves service quality but also strengthens legal protection. The application of artificial intelligence in dental practice can enhance legal protection for patients by improving service quality and reducing the risk of medical errors. From a positivist perspective, the use of this technology aligns with legal principles aimed at protecting patients' rights and ensuring justice in medical practices.